2015
DOI: 10.1111/1471-0307.12219
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of bovine milk with vegetable milk: Effects on the survival of probiotics and rheological and physicochemical properties of frozen fermented dessert

Abstract: In this study, frozen fermented desserts containing Lactobacillus acidophilus (La-05; L) and Bifidobacterium bifidum (Bb-12; B), were made from bovine (W), soya (S), coconut (C) and composite (i.e. combinations of coconut or bovine milks with soya milk) milks. The changes in frozen dessert eating qualities and the survival of added microbes were evaluated. The highest viscosity and melting resistance, and the lowest total sensory scores, were found in the products made using soya milk. After 90-day storage at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
11
1
Order By: Relevance
“…Aboulfazli et al . (), who used vegetable milk, reported 2.2% protein for soya milk and 3.4% for coconut milk, while fat content ranged between 2.0 and 19% with pH of 6.0–7.0. Bernat et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aboulfazli et al . (), who used vegetable milk, reported 2.2% protein for soya milk and 3.4% for coconut milk, while fat content ranged between 2.0 and 19% with pH of 6.0–7.0. Bernat et al .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in order to determine the acceptance of the yoghurt, the sensory evaluation of the selected drinks was based on affective tests by using a 9-point hedonic scale, 1 for dislike extremely and 9 for like extremely (Donkor et al 2007 Both extracts had significant differences (P < 0.05) in protein content, moisture, pH and colour parameters (L*, a* and b*). Aboulfazli et al (2014), who used vegetable milk, reported 2.2% protein for soya milk and 3.4% for coconut milk, while fat content ranged between 2.0 and 19% with pH of 6.0-7.0. Bernat et al (2015) developed a nondairy probiotic fermented beverage in which they measured the following values: protein 1.4%, fat 3.9%, ash 0.32% and moisture 93.4%.…”
Section: Sensory Analysismentioning
confidence: 99%
“…It provides an inexpensive source of dietary protein and has been processed to make different kinds of soy foods. Soya milk is considered as suitably alternative dairy product, especially for lactose‐intolerant or vegetarian individuals, which provides high‐quality protein and isoflavone (Aboulfazli et al , ; Karaçalı et al , ). Specifically, tofu (soya bean curd), as the most consumed soya product in Asia, is prepared by curdling heated soya milk with proper coagulants.…”
Section: Introductionmentioning
confidence: 99%
“…Coconut milk replacing dairy milk was attempted in yogurt (Siripanporn et al, 2000) and fermented ice cream (Aboulfazli et al, 2016). Coconut milk yogurt was stable without syneresis for 14 days when stored at 4 -10°C, whereas the texture of coconut milk yogurt had higher panelists score than dairy milk (Siripanporn et al, 2000).…”
Section: Introductionmentioning
confidence: 99%